The Effect of Systematic Incremental Contextual Interference on Learning Different Generalized Motor Program (Volleyball Service) - Saeed Nazari; Rasool Hemayattalab; Mahmood Sheikh; Morteza Homayounnia (University of Tehran, 2015)
This study aimed at investigating the effect of blocked, incremental systematic and random contextual interferences on acquisition, retention and transfer of volleyball skills based on changes in a generalized motor program. In fact, this study was conducted to answer this question that whether regular increment of contextual interference level is more effective on learning volleyball service skill than blocked or random practice schedules. 30 students (mean age 23±4 yr, 3 groups and each 10 subjects) participated in this study. The groups were different in practices of the three services. Subjects performed simple, overhead and single arm skills from a distance (9 m from the volleyball net) with different practices. Each participant practiced 108 trials of each service, totally 324 trials during 9 sessions (each session 36 trials). The results indicated that incremental practice resulted in a better performance in retention and transfer tests than blocked and random practices (P˂0.05). In general, it was suggested that the practice should be scheduled so that it can start from low interference and gradually and systematically continues towards high interference in order to facilitate learning of several generalized motor skills.